Human Value Management: The influence of the contemporary developments of corporate social responsibility and social capital on HRM - Michiel Schoemaker; André Nijhof; Jan Jonker (Management Revue, 2006)
In both practice-oriented and academic discourses the concepts of corporate social responsibility (CSR) and human resource management (HRM) are often treated separately. It is argued here that this is an outdated approach. Starting from the observation that organisations develop towards open systems, it becomes obvious that CSR and HRM are intertwined. In open systems cooperative action is based on the willingness of humans to bring in and develop their talents as part of communities of work. The proper functioning of organisations becomes dependent on shared values between networks of people. At the same time these networks broaden the perception of what (new) roles and functions organisation should fulfil. This brings in the notion of CSR. Organisations are expected to encompass a broadening range of responsibilities combining the delivery of added value in the market place with broadening responsibilities. These developments require a repositioning of the role and perception of HRM towards a new strategic approach labelled here as Human Value Management. This paper offers an exploration of this HVM approach by comparing it to HRM and linking it to CSR. As such it offers a conceptual framework enabling the formulation of a series of questions for future research.
Keywords: 650; Human Value Management; Human Resource Management; social capital; corporate social responsibility; Personalmanagement; Social Capital; Corporate Social Responsibility; Unternehmensethik